THE EFFECT OF USING KAHOOT APPLICATION TO IMPROVE THE VOCABULARY ABILITY OF SEVENTH GRADE STUDENTS OF SMP NEGERI MADANI PEKANBARU - Safitri, Ii Nanda; Prawati, Atni; Aruan, Rumiri Rotua (TELL - US JOURNAL, 2025)
The integration of technology in education has encouraged the use of various digital applications to enhance learning effectiveness, one of which is the Kahoot application. Although technology is increasingly used in classrooms, its effectiveness in improving students’ vocabulary remains underexplored. This research aims to determine whether the use of the Kahoot application has a significant effect on students’ vocabulary ability. A quantitative approach was applied using a quasi-experimental design. The sample consisted of 52 seventh-grade students of SMP Negeri Madani Pekanbaru, divided into an experimental class using the Kahoot application for vocabulary learning and a control class taught using conventional methods. Data were collected through pre-tests and post-tests to assess vocabulary performance before and after the treatment, which was administered four times. The analysis revealed a significant difference between the experimental and control classes after the treatments. The results showed that the post-test score of the experimental class (77.03) was higher than that of the control class (57.51). Furthermore, the findings indicated a significance level of α = 0.05 with p = 0.001 (p < α), which means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. This result is supported by an effect size of 0.95, indicating that the use of the Kahoot application had a moderate effect on students’ vocabulary ability.